Brachial-ankle pulse wave velocity as a predictor of long-term cardiovascular events in 2174 subjects with type 2 diabetes mellitus: A retrospective cohort study. Issue 45 (11th November 2022) - Kim, Hack-Lyoung; Jeon, Won Kyeong; Joh, Hyun Sung; Lim, Woo-Hyun; Seo, Jae-Bin; Kim, Sang-Hyun; Zo, Joo-Hee; Kim, Myung-A
Abstract : The prognostic value of arterial stiffness in patients with diabetes mellitus (DM) remains unclear. The aim of this study was to investigate the association between brachial-ankle pulse wave velocity (baPWV) and the occurrence of cardiovascular events in people with DM. A total of 2714 subjects (mean age, 63.6 years; males, 59.3%) with type 2 DM and without documented cardiovascular disease and stroke were analyzed. The primary end-point of this study was composite cardiovascular events of cardiac death, non-fatal myocardial infarction, coronary revascularization and stroke. There were 118 composite events (4.3%) during a median follow-up period of 3.84 years (interquartile range, 1.60–5.52 years). In multivariable Cox regression analysis, higher baPWV (≥1672 cm/s) was associated with composite events even after controlling for potential confounders (hazard ratio [HR], 2.00; 95% confidence interval [CI], 1.31–3.07; P = .001). Compared to the lowest baPWV tertile, both middle (HR, 1.84; 95% CI, 1.03–3.27; P = .037) and the highest (HR, 2.97; 95% CI, 1.69–5.22; P < .001) tertile of baPWV were associated with increased risk of cardiovascular events in the same multivariable model. In conclusion, the baPWV was associated with cardiovascular events in people with type 2 DM. Considering the simplicity and convenience of baPWV measurement, baPWV may be useful for risk stratification of people with type 2 DM.